BOOK REVIEW OF THE CHRONICLES OF NARNIA, THE LAST BATTLE WRITTEN BY C. S LEWIS - Bunda, Nenden Lovenia (LANTERN (Journal on English Language, Culture and Literature), 2016)
Literary work can be divided into several different types such as novel, poem and drama. Each of type has its own readers with specific reason why they like novel, poem or drama. One of the most interesting genres that we ever read is children’s literature. Children’s literature presents magical and attractive story and becomes our favorite things during our childhood. The story in children’s literature can always amaze us in past, present, and future time, at the same time it can also teach us about moral values.